An Empirical Research on the Relationship Between Employee Boreout and Performance: Mediating Role of Procrastination - Al-Mashadani, Hadeel (Archives of Business Research, 2022)
The purpose of this study was to discover whether employee boreout was related to employee task performance and whether employee procrastination was mediating this relationship. In order to achieve that, a cross-sectional research has been conducted. The data were collected from 400 employees who work in a telecommunication company operating in Dubai, the United Arab Emirates, using the survey technique, between the 16th of July and the 19th of August, 2022. Linear regression tests were used to analyze the collected data. Findings showed that there was a negative relationship between the crisis of meaning and task performance, job boredom and task performance, and the crisis of growth and task performance. This study also indicated that there was a positive relationship between procrastination and the crisis of meaning, job boredom, and the crisis of growth. Finally, it was revealed for the first time that procrastination was mediating the relationship between employee boreout and task performance.